(2^2 + 1)(2^4 +1)(2^8 +1)(2^16 + 1)(2^32 + 1)(2^64 + 1) - 1/3 • 2^128

tanya2017kazanova tanya2017kazanova    2   18.05.2019 20:15    0

Ответы
ГлебGleb39 ГлебGleb39  12.06.2020 03:03

(2^2+1)(2^4+1)(2^8+1)(2^{16}+1)(2^{32}+1)(2^{64}+1)=

=\frac{(2^2-1)(2^2+1)(2^4+1)(2^8+1)(2^{16}+1)(2^{32}+1)(2^{64}+1)}{2^2-1}=

=\frac{(2^4-1)(2^4+1)(2^8+1)(2^{16}+1)(2^{32}+1)(2^{64}+1)}{3}=\frac{(2^8-1)(2^8+1)(2^{16}+1)(2^{32}+1)(2^{64}+1)}{3}=

=\frac{(2^{16}-1)(2^{16}+1)(2^{32}+1)(2^{64}+1)}{3}=\frac{(2^{32}-1)(2^{32}+1)(2^{64}+1)}{3}=\frac{(2^{64}-1)(2^{64}+1)}{3}=\frac{2^{128}-1}{3}.

Вывод: все выражение равно \frac{2^{128}-1}{3}-\frac{2^{128}}{3}=-\frac{1}{3}.

ответ: -\frac{1}{3}

ПОКАЗАТЬ ОТВЕТЫ